The lasting impact of parental early life malnutrition on their offspring: Evidence from the China Great Leap Forward Famine - KIM, Seonghoon (Institutional Knowledge at Singapore Management University, 2014)
We investigate whether the effects of parents’ in utero malnutrition extend to the second generation (their children). Specifically, we explore whether the second generation’s level of schooling is negatively impacted by their parents’ malnutrition in utero, using the China Famine as a natural experiment. We find that, the impact of mother’s in utero malnutrition due to the Famine reduced second generation male and female entrance into junior secondary school by about 5–7 percentage points. We measure famine severity with provincial excess death rates instrumented by measures of adverse climate conditions, which corrects for possible biases induced by measurement errors and omitted variables. Our findings indicate the existence of an important second-generation multiplier of policies that support the nutrition of pregnant women and infants in any country where nutritional deficiencies remain today.